Implementasi Pembelajaran Project based learning untuk Menumbuhkan Kemampuan Berpikir Kritis Anak Usia 5-6 Tahun - Suharni Suharni; Isdayanti Hondro; Elizabeth Marbun; Sri Meisyanti Nababan; Amanda Rafmandini (Indonesian Journal Publisher, 2026)
Critical thinking skills are one of the abilities that need to be developed in early childhood. One of the learning models that can be used to support the development of these abilities is Project-Based Learning (PjBL). This study aims to determine the implementation of the Project-Based Learning model in fostering the critical thinking skills of children aged 5–6 years in PAUD Kalam Kudus. This study uses a descriptive qualitative approach. Data were collected through observation and interviews with teachers and principals. The results of the study show that the implementation of PjBL is carried out through several stages, namely determination of project themes, activity planning, project implementation, presentation of results, and reflection. Through simple project activities such as getting to know plants, children are seen to be more active in observing, asking questions, exploring, and expressing opinions. In addition, project activities also help develop children's social and communication skills through cooperation with peers. The teacher plays the role of a facilitator who guides the child during the learning process. Based on the results of the research, it can be concluded that the Project-Based Learning model can help foster early childhood critical thinking skills and create a more active and meaningful learning process.